Integrating Sustainable Development And Poverty Reduction: A Model For Central Aceh Regency - Khairuddin Khairuddin; Lia Nazliana Nasution; Rusiadi Rusiadi; Bhaktiar Efendi; Suhendi Suhendi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the contribution and dynamic interrelationships among key socio-economic variables influencing poverty and human development in Indonesia, using the Forecast Error Variance Decomposition (FEVD) approach within a simultaneous equation framework. The variables analyzed include poverty, unemployment, labor force participation rate (LFPR), per capita income, and the Human Development Index (HDI). The results reveal that poverty is primarily influenced by lagged values of per capita income and HDI. Meanwhile, unemployment is significantly affected by poverty and LFPR. LFPR itself is influenced by poverty, while per capita income is impacted by unemployment. HDI is significantly driven by poverty and per capita income. These findings confirm that the interactions among variables are simultaneous and can mutually reinforce or weaken each other. Therefore, policies aimed at poverty alleviation and human development enhancement must be designed in an integrated and cross-sectoral manner. A multidimensional approach that considers the historical interlinkages among variables is essential for formulating inclusive, sustainable, and evidence-based development strategies. This study offers both theoretical and practical contributions to socio-economic policymaking, particularly in the context of green and digital development in Indonesia.